ON THE RELATIONSHIP BETWEEN EFFICIENCY OF UTILIZATION OF NITROGEN, PHOSPHORUS AND POTASSIUM BY SEVERAL BEAN VARIETIES (ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.) AND YIELD POTENTIAL - Malavolta, E.; Sobrinho, M. O. C. Brasil; Rezende, H. E. C.; Vitti, G. C.; Amaral, F. A. L. (REVISTA DE AGRICULTURA, 2020)
ON THE RELATIONSHIP BETWEEN EFFICIENCY OF UTILIZATION OF NITROGEN, PHOSPHORUS AND POTASSIUM BY SEVERAL BEAN VARIETIES (ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.) AND YIELD POTENTIAL